THE INFLUENCE OF PERCEIVED VALUE AND TRUST ON REPURCHASE INTENTION IN SHOPEE ONLINE SHOPPING - Pardede, Christine R.; Lapian, S.L.H.V Joyce; Pandowo, Merinda . (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract: Shopee is one of many online shopping center in Indonesia. Many people like to buy in Shopee because all the products are usually cheaper than at the stores itself. The purpose of this research is to find out the influence of perceived value and trust on repurchase intention in Shopee online shopping. The population of this research is all the customers of Shopee Online Shop from Manado. The sample of this research is customers of Shopee as many as 100 respondents, who already bought in Shopee 2 times or more, which are using purposive sampling. The data is analyzed by quantitative method and it is a causal research, and was using multiple linear regression analysis and processing of data using SPSS statistical program. Based on the results, research findings show that perceived value (X1) and trust (X2) proved significantly influence on repurchase intention (Y) in Shopee Online Shop. This means that the company has a good participant on people in online shopping industry. Recommendation for Shopee itself that Shopee should maintain their products so the customers repurchase intention could be increased as the perceived value and trust of the customer also increased.Keywords: perceived value, trust, repurchase intentionAbstract: Shopee is one of many online shopping center in Indonesia. Many people like to buy in Shopee because all the products are usually cheaper than at the stores itself. The purpose of this research is to find out the influence of perceived value and trust on repurchase intention in Shopee online shopping. The population of this research is all the customers of Shopee Online Shop from Manado. The sample of this research is customers of Shopee as many as 100 respondents, who already bought in Shopee 2 times or more, which are using purposive sampling. The data is analyzed by quantitative method and it is a causal research, and was using multiple linear regression analysis and processing of data using SPSS statistical program. Based on the results, research findings show that perceived value (X1) and trust (X2) proved significantly influence on repurchase intention (Y) in Shopee Online Shop. This means that the company has a good participant on people in online shopping industry. Recommendation for Shopee itself that Shopee should maintain their products so the customers repurchase intention could be increased as the perceived value and trust of the customer also increased.Keywords: perceived value, trust, repurchase intention